Pengaruh Daya Tarik Wisata, Electronic Word of Mouth dan Citra Destinasi Terhadap Keputusan Berkunjung Objek Wisata Heha Sky View Kabupaten Gunungkidul - Amalino Lutfi Cheila Putranti; Nur Rokhman (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2023)
This study aims to determine the effect of tourist attraction, electronic word of mouth and destination image on the decision to visit the Heha Sky View tourist attraction, Gunungkidul Regency. This research was conducted in December 2022 with data collection using a questionnaire. The population in this study were visitors to Heha Sky View. The sample in this study is only Heha Sky View visitors in 2022 with a minimum age of 17 years. The data obtained were 152 respondents. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that tourist attraction has a positive and significant effect on visiting decisions, electronic word of mouth has a positive and significant effect on visiting decisions, destination image has a positive and significant effect on visiting decisions.